Turbulent electromagnetic fields at sub-proton scales: Two-fluid and full-kinetic plasma simulations - González, C. A. (2019)
Plasma dynamics is a multi-scale problem that involves many spatial and temporal scales. Turbulence connects the disparate scales in this system through a cascade that is established by nonlinear interactions. Most astrophysical plasma systems are weakly collisional, making a fully kinetic Vlasov description of the system essential. The use of reduced models to study such systems is computationally desirable, but careful benchmarking of physics in different models is needed. We perform one such comparison here between the fully kinetic Particle-In-Cell model and a two-fluid model that includes Hall physics and electron inertia, with a particular focus on the sub-proton scale electric field. We show that in general, the two fluid model captures large scale dynamics reasonably well. At smaller scales, the Hall physics is also captured reasonably well by the fluid code, but electron features show departures from the fully kinetic model. Implications for the use of such fluid models are discussed.